2022
DOI: 10.1186/s12893-022-01712-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgically managed symptomatic intraspinal lumbar facet synovial cyst outcome of surgical treatment with resection and instrumented posterolateral fusion, a case series

Abstract: Background There is controversy regarding the treatment of symptomatic synovial cysts, specifically, the need for a concomitant fusion when surgical resection of the synovial cysts is required. We present a retrospective review of a series of patients treated for symptomatic synovial cysts of the lumbar region during the last 20 years by a single surgeon, analyzing the current available literature. Methods Retrospective review. The same surgical te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…(2022) observed that 100% of 69 patients with LSC failed to improve following 3 months of non-surgical management; all 69 underwent decompressions/instrumented posterolateral lumbar fusions that resulted in no LSC recurrence [ Table 1 ]. [ 11 ] Further, utilizing Macnab’s Outcomes Criteria, 91.3% demonstrated good/excellent results (63 patients), with only 8.6% (6 patients) showing fair/poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2022) observed that 100% of 69 patients with LSC failed to improve following 3 months of non-surgical management; all 69 underwent decompressions/instrumented posterolateral lumbar fusions that resulted in no LSC recurrence [ Table 1 ]. [ 11 ] Further, utilizing Macnab’s Outcomes Criteria, 91.3% demonstrated good/excellent results (63 patients), with only 8.6% (6 patients) showing fair/poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Lumbar synovial cysts (LSC), best diagnosed on MR studies, may cause symptoms ranging from unilateral radiculopathy to cauda equina syndromes/compression [Table 1]. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Typically, attempts at percutaneous cyst aspiration, injection (i.e. with/without steroids/other), dilatation, and/or disruption typically fail.…”
Section: Introductionmentioning
confidence: 99%
“…However, neurogenic claudication, neurological deficit, and cauda equina compromise have also been reported. 2,5,7,[9][10][11] The spinal ganglia occurred most frequently in the 6th decade of life with a slight female predominance. [2][3][4][5]9,11,12 It can be unilateral, bilateral at a single or multilevel, and the majority are asymptomatic, incidentally found on magnetic resonance imaging (MR).…”
Section: Introductionmentioning
confidence: 99%
“…2,5,7,[9][10][11] The spinal ganglia occurred most frequently in the 6th decade of life with a slight female predominance. [2][3][4][5]9,11,12 It can be unilateral, bilateral at a single or multilevel, and the majority are asymptomatic, incidentally found on magnetic resonance imaging (MR). 3,4,7,12,13 The conservative treatment has short-term or no clinical improvement so decompression and surgical excision are the preferred choices in symptomatic patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation